O longo caminho: guerreiro ramos e a sociologia da administração antes de a nova ciência das organizações - Bariani, Edison [UNESP] (Escola de Administração da Universidade Federal da Bahia, 2010)
Before exiling to the U.S.A. and elaborating his theoretical constructions around the administration in contemporary society, which culminated with the publication of The new science of the organizations (in 1981), Guerreiro Ramos had already accomplished much. From his early works on administration (in the Department of Administration of the Public Service, DASP, in the 1940's) to his work that preceded his exile, Administration and strategy of the development (in 1966), he reflected on administration, rationality and bureaucracy in a context of searching for modernization. Such reflections (and frustrations) characterized his intellectual development, his criticisms of rationality (instrumental) and his considerations about a humanistic view of administration, a central issue in his theoretical work in The new science of the organizations.

Antes de se exilar nos EUA e elaborar suas construções teóricas em torno da administração na sociedade contemporânea - que culminou com a publicação de A nova ciência das organizações (em 1981) - Guerreiro Ramos percorreu longo caminho. Desde seus primeiros trabalhos sobre administração (no Departamento de Administração do Serviço Público, DASP, na década de 1940), até sua obra que precedeu o exílio, Administração e estratégia do desenvolvimento (em 1966), Guerreiro refletiu sobre a administração, racionalidade e burocracia num contexto de busca pela modernização. Tais reflexões (e frustrações) subsidiaram sua formação intelectual, sua crítica posterior à racionalidade (instrumental) e suas considerações para uma visão humanista da administração, questão central nos seus esforços teóricos empreendidos em A nova ciência das organizações.
The long way: guerreiro Ramos and sociology of management before the new science of organizations
Keywords: Guerreiro Ramos; Administração; Burocracia; Modernização; Guerreiro Ramos; Administration; Bureaucracy; Modernization